2016
DOI: 10.1080/09658211.2016.1224358
|View full text |Cite|
|
Sign up to set email alerts
|

Word frequency influences on the list length effect and associative memory in young and older adults

Abstract: Many studies show that age deficits in memory are smaller for information supported by pre-experimental experience. Many studies also find dissociations in memory tasks between words that occur with high and low frequencies in language, but the literature is mixed regarding the extent of word frequency effects in normal ageing. We examined whether age deficits in episodic memory could be influenced by manipulations of word frequency. In Experiment 1, young and older adults studied short and long lists of high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…In addition to these semantic predictors, COCA frequency and name agreement also predicted memory. COCA frequency of a concept positively predicted both lexical HRs and FARs, (HRs: β = 0.008, t = 1.93, p = 0.05; FAR: β = 0.02, t = 3.72, p = 0.0002), in keeping with the notion that highfrequency items are more likely to be endorsed as "old" (Badham et al, 2017); no effect of Frequency was seen for visual memory. Name agreement was predictive of memory in the visual memory task (HRs: β = 0.06, t = 3.76, p = 0.0002; FAR: β = 0.03, t = 2.03, p = 0.04) and the lexical memory task (HR: β = 0.12, t = 7.99, p < 0.00001; FAR: β = 0.04, t = 2.87, p = 0.004).…”
Section: Linear Models Of Memorabilitysupporting
confidence: 64%
“…In addition to these semantic predictors, COCA frequency and name agreement also predicted memory. COCA frequency of a concept positively predicted both lexical HRs and FARs, (HRs: β = 0.008, t = 1.93, p = 0.05; FAR: β = 0.02, t = 3.72, p = 0.0002), in keeping with the notion that highfrequency items are more likely to be endorsed as "old" (Badham et al, 2017); no effect of Frequency was seen for visual memory. Name agreement was predictive of memory in the visual memory task (HRs: β = 0.06, t = 3.76, p = 0.0002; FAR: β = 0.03, t = 2.03, p = 0.04) and the lexical memory task (HR: β = 0.12, t = 7.99, p < 0.00001; FAR: β = 0.04, t = 2.87, p = 0.004).…”
Section: Linear Models Of Memorabilitysupporting
confidence: 64%
“…(This contrasts with output-bound accuracy, which can measure the correctness of memory report; see the Supplementary Materials.) Others, however, have also reported absolute recall in list-length experiments (e.g., Badham et al, 2017;Ward, 2002) and found that the number of correctly recalled items increases as list-length increases. We focused here on the number of correctly recalled words, not the proportion, for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there is evidence that low frequency words improve retrieval on certain task. Badham et al (2017) investigated low and high frequency words in an itembased and associative-recognition memory test in younger and older adults. The researchers found that both groups remembered more high frequency words on the associative test and more low frequency words on the itembased test.…”
Section: Healthy Ageing and Light Verbsmentioning
confidence: 99%